Germinating seeds or bulbils in 87 of 113 tested Arctic species indicate potential for ex situ seed bank storage - Alsos, Inger Greve; Müller, Eike; Eidesen, Pernille Bronken (Polar Biology, 2013)
Arctic plant species are expected to lose range due to climate change. One approach to preserve the genetic and species diversity for the future is to store propagules in seed vaults. However, germinability of seeds is assumed to be low for Arctic species. We evaluated ex situ storage potential of 113 of the 161 native angiosperms of Svalbard by studying seed ripening and germination. Seeds or bulbils were collected, and germinability was tested after one winter of storage in the Svalbard Global Seed Vault. Twenty-six of the species did not produce ripe propagules, 8 produced bulbils, and 79 produced seeds. Bulbils sprouted to high percentages. Seeds of 10 species did not germinate, 22 had low germination (<20 %), 34 had germination of 21–70 %, and 13 had high germination percentages (>70 %). More than 70 % of the species belonging to Asteraceae, Brassicaceae, Caryophyllaceae, Juncaceae, Rosaceae, and Saxifragaceae germinated. Cold tolerant, common species had higher germination percentages than relatively thermophilous, rare species. Germination percentages were six times higher than observed in 1969 (n = 51) and 0.7 times that observed in 2008 (n = 22), indicating that recent climate warming improves germination in the Arctic. While in situ conservation is of vital importance, ex situ conservation in seed banks is a potential complementary conservation strategy for the majority of Arctic vascular plant species. For species that did not germinate, other methods for ex situ conservation should be sought, for example, growing in botanical gardens.